ANALYSIS OF MYCOPLASMA GALLISEPTICUM INFECTION FACTORS IN COMMERCIAL LAYER CHICKEN FARM USING ANALYTICAL HIERARCHY PROCESS - Diyantoro, Diyantoro; Pribadi, Eko Sugeng (Faculty of Vocational Studies, Universitas Airlangga, 2017)
Background: Mycoplasma galliseptium (MG) is a pathogenic microbial often found in poultry farm industry. In Indonesia there are rarely data of MG research. There are some factors increased the risk of MG infection. Purpose: This research aimed to determine the factors involved in the transmission of MG in commercial layer chicken farm. Method: This was a descriptive research with the data was collected from pairwise comparison questionnaire distributed to poultry expert. The Data was analyzed using Analytical Hierarchy Process (AHP) supported by computer programme